A concise survey of advancements in recovery strategies for resilient complex networks. (25th September 2018) - Afrin, Tanzina; Yodo, Nita
Abstract: The vulnerability of complex networks is a matter of great concern nowadays because of the probable occurrence of network failures due to inevitable disruptive events. To resume full operations of the complex networks after such failures, it is crucial to develop a resilient complex network. As a lot of researchers have realized this necessity and contributed to this field, a large variety of recovery strategies have been proposed under different circumstances. Recovery strategies may vary based on the characteristics of the complex networks, the behaviours of the failures and the aftereffects of the failures. The presence of diversity in various recovery strategies challenges the development of a more generalized network recovery strategy that could be implemented in a wider application range. This article provides a compilation of the advancements in the existing recovery strategies, particularly in complex networks application. The characteristics of different complex networks and their dynamic failure behaviours are presented along with their currently available network recovery strategies. Some future research directions in finding more refined yet generalized recovery strategies with the perspective of resilience are identified. This article encourages the development of more advanced recovery strategies to mitigate the performance loss in resilient complex networks against the inevitable failures.